Precision Medicine: An Introduction. Issue 3 (2nd October 2017) - Prince, J. Dale
ABSTRACT: Precision medicine is an emerging approach for disease treatment and prevention that takes into account individual variability in genes, environment, and lifestyle. With the precision medicine initiative push from the U.S. federal government, precision medicine has become an important concept for biomedical health researchers, practitioners, and librarians. This article explores, in brief, the concept, its history, components, National Institutes of Health (NIH) initiatives, and challenges.